An integrated semi-continuous culture to treat original swine wastewater and fix carbon dioxide by an indigenous Chlorella vulgaris MBFJNU-1 in an outdoor photobioreactor. (November 2021) - Zheng, Mingmin; Dai, Jingxuan; Ji, Xiaowei; Li, Daogui; He, Yongjin; Wang, Mingzi; Huang, Jian; Chen, Bilian
Graphical abstract: Highlights: A semi-continuous process was applied to treat original swine wastewater and fix CO2 . The process was mediated with Chlorella vulgaris MBFJNU-1 in outdoor photobioreactors. Microalga at 80% renewal rate had the best ability to treat wastewater and fix CO2. Abstract: This work was the first time to evaluate the ability of an isolated Chlorella vulgaris MBFJNU-1 to remove nutrients of original swine wastewater (OSW) and fix carbon dioxide (CO2 ) under outdoor conditions in a simultaneous manner using column photobioreactors. The results showed that microalga cultivated at 3% CO2 in a batch mode achieved the highest biomass and CO2 fixation rate. Then, a semi-continuous process for OSW treatment and CO2 fixation simultaneously by microalga was established and the renewal rate of this process was deeply investigated. Microalga cultivated at 3% CO2 and 80% renewal rate gave the highest productivities of total biomass, CO2 fixation and the greatest average removal rates of total nitrogen, N-NH4 +, total phosphorus and chemical oxygen demand. Taken together, C. vulgaris MBFJNU-1 was the promising microalga under outdoor conditions for swine wastewater treatment and CO2 fixation simultaneously for biofuels and biofertilizer production.